2018
DOI: 10.1080/14786419.2018.1543682
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation

Abstract: Chemical characterization of constituents fromPolygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation Twenty-four compounds were isolated from the roots of Polygonatum cyrtonema Hua, including a new octopamine dimer, named trans-bis(N-feruloyl)octopamine (1). The structure was established on the basis of spectroscopic and chemical methods. All the extracts and compounds were evaluated for cytotoxic and antioxidant activities by using MTT and chemiluminescence assay. The extracts showed activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Currently, many TCM preparations containing Da Huang, have been clinically used for treating liver diseases, inflammation and cancer (Li et al, 2007;Li et al, 2009). Moreover, a large number of studies in vitro and in vivo have reported that Da Huang, TCM preparations containing Da Huang, the Da Huang extracts and the major anthraquinone compounds derived from Da Huang (such as emodin, rhein, aloe-emodin) have therapeutic potential in the treatment of hepatocellular carcinoma (Kupchan and Karim, 1976;Ha et al, 2004;Cao et al, 2005;Cha et al, 2005;Kim et al, 2005;Huang et al, 2007;Lu et al, 2007;Shi et al, 2008;Lin et al, 2009;Tsai et al, 2013;Lin et al, 2016;Lee et al, 2017;Tan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many TCM preparations containing Da Huang, have been clinically used for treating liver diseases, inflammation and cancer (Li et al, 2007;Li et al, 2009). Moreover, a large number of studies in vitro and in vivo have reported that Da Huang, TCM preparations containing Da Huang, the Da Huang extracts and the major anthraquinone compounds derived from Da Huang (such as emodin, rhein, aloe-emodin) have therapeutic potential in the treatment of hepatocellular carcinoma (Kupchan and Karim, 1976;Ha et al, 2004;Cao et al, 2005;Cha et al, 2005;Kim et al, 2005;Huang et al, 2007;Lu et al, 2007;Shi et al, 2008;Lin et al, 2009;Tsai et al, 2013;Lin et al, 2016;Lee et al, 2017;Tan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In TCM, PS was first recorded by Mingyi Bielu , and was listed to the “Top Grade” herb in Shennong Bencao Jing ( Zhao et al, 2018 ; Han et al, 2020 ). As a “medicine food homology” plant, many bioactive ingredients have been confirmed in PS, including polysaccharides, steroidal saponins, amino acids, flavonoids, anthraquinones, and alkaloids ( Zeng et al, 2020 ). Modern pharmacological studies have demonstrated that PS decreases blood glucose ( Ma et al, 2022 ) and blood pressure ( Su et al, 2022 ), prevents atherosclerosis ( Zhu et al, 2015 ), enhances immunity ( Sun et al, 2022 ), and has anti-fatigue ( Shen et al, 2021 ), anti-tumor ( Li et al, 2022 ), and anti-aging effects ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Steroidal saponins are characterized by a skeleton derived from oxidosqualene, consisting of a sugar moiety linked to a steroidal (27 carbon atoms) aglycone [6]. Steroidal saponins have attracted extensive attention owing to their excellent anti-bacterial, anti-inflammatory, and anti-oxidation effect and the potential for alleviating diabetes and other metabolic disorders [5,7,8]. Steroidal saponins have been extensively used in the food, medicine, fodder, and cosmetics industries [9].…”
Section: Introductionmentioning
confidence: 99%